2014
DOI: 10.1089/ars.2013.5665
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Plant Development

Abstract: The multiple roles of reactive oxygen species in the control of plant growth and development have been identified, but increasing emphasis should now be placed on the functions of redox-regulated proteins, along with the central roles of reductants such as NAD(P)H, thioredoxins, glutathione, glutaredoxins, peroxiredoxins, ascorbate, and reduced ferredoxin in the regulation of the genetic and epigenetic factors that modulate the growth and vigor of crop plants, particularly within an agricultural context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
176
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(184 citation statements)
references
References 201 publications
7
176
0
1
Order By: Relevance
“…It is thus likely that growing shoot tissues and meristems exhibit anoxic conditions: multiple reports have shown a relationship between ROS levels and root development, but less attention has been dedicated to the link between ROS levels and shoot meristematic functions. However, work in perennial species had suggested that bud break after winter dormancy is associated with strong increases in ROS levels (Considine and Foyer, 2014). We explored the similarities between dormancy and GPA: gene expression changes from growing to arrested meristems and vice versa are consistent with the idea that GPA represents a shoot dormancy.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It is thus likely that growing shoot tissues and meristems exhibit anoxic conditions: multiple reports have shown a relationship between ROS levels and root development, but less attention has been dedicated to the link between ROS levels and shoot meristematic functions. However, work in perennial species had suggested that bud break after winter dormancy is associated with strong increases in ROS levels (Considine and Foyer, 2014). We explored the similarities between dormancy and GPA: gene expression changes from growing to arrested meristems and vice versa are consistent with the idea that GPA represents a shoot dormancy.…”
Section: Discussionmentioning
confidence: 80%
“…To our knowledge, such extreme differences in ROS levels have not been described in Arabidopsis inflorescences upon growth transitions. Instead, they are reminiscent of effects previously described in transitions in to and out of bud dormancy in other species, such as kiwifruit, grapevine, and poplar (Considine and Foyer, 2014).…”
Section: Gpa Is Associated With Responses To Stress and To Growth-inhmentioning
confidence: 81%
“…The subsequent question that arises is how this regulation is mediated. It was discussed previously that hypoxiamediated changes in the redox status of the cell could be involved in regulating low-oxygen stress responses (Considine and Foyer, 2014). Although it is not possible to fully answer the question of how the tricarboxylic acid cycle is controlled upon hypoxia with our current experimental data, our results provide interesting indications that give rise to the hypothesis that redox-mediated control of the tricarboxylic acid cycle might be involved.…”
Section: Hypoxia Leads To the Inhibition Of Sdh And Concomitantly Of mentioning
confidence: 99%
“…A loss of dehydration tolerance on the fifth day following imbibition is accompanied by a higher AsA content and AsA/DHA ratio in 6-day-old seedlings compared to 4-day-old seedlings. The higher AsA content may be because of the de novo biosynthesis of AsA required for both cell division and expansion (Considine and Foyer 2014) and a higher AsA recycling ability. In response to water deficiency, seedlings resistant to dehydration demonstrated a steady reduced status of ascorbate because of the paralleled increase in DHA and AsA.…”
Section: Discussionmentioning
confidence: 99%
“…The differential response of ascorbate and glutathione to environmental factors illustrates the specific and distinct roles played by AsA and GSH within plants. AsA regulates primarily plant development and GSH is involved in plant development and in stress defence and signalling (Considine and Foyer 2014).…”
Section: Discussionmentioning
confidence: 99%